Efektivitas Didecyldimethylammonium Chloride 2.5% dan Chlorine 0.5% terhadap Pertumbuhan Staphylococcus aureus dan Klebsiella pneumoniae di Ruang Operasi - Jumanto Jumanto; Abu Bakar; Achmad Sigit Sugiharto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effectiveness of the disinfection of 0.5% chlorine and 2.5% didecyldimethylammonium chloride against Staphylococcus aureus and Klebsiella pneumoniae in the operating room. The method used is a quasi-experimental post-only group design with a total sample of 40 samples of the operating room environment. The results showed no difference between the two types of disinfectants, namely didecyldimethylammonium chloride 2.5% and chlorine 0.5% in reducing the number of bacteria (p-value 0.373) and both were able to reduce the number of Staphylococcus aureus and Klebsiella pneumoniae. In conclusion, both disinfectants effectively reduced Staphylococcus aureus and Klebsiella pneumoniae on operating room surfaces. Keywords: Didecyldimethylammonium Chloride Disinfection, Chlorine, Bacterial Growth, Operating Room